The Role of Guidance and Counseling Teachers in Improving Students’ Time Discipline at SMPK St. Theresia Kupang - Mekiani Guntrima Mogi Sile; Stefanus Lio (The Future of Education Journal, 2025)
Time discipline is a fundamental aspect in shaping students’ character and academic success. This study is motivated by the phenomenon of low time discipline among students at SMPK St. Theresia Kupang, which affects learning regularity and instructional effectiveness. The purpose of this study is to analyze the strategic role of Guidance and Counseling (BK) teachers in improving students’ time discipline through the implementation of understanding, prevention, development, and corrective functions based on professional regulatory frameworks. This research employed a qualitative approach using both library and field studies. The informants consisted of one BK teacher and six students selected through purposive sampling techniques. Data were collected through semi-structured interviews, documentation, and literature review, then analyzed using the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The findings indicate that classical guidance services, group guidance using self-management techniques, and individual counseling based on Cognitive Behavior Therapy (CBT) are effective in enhancing students’ awareness and responsibility toward time management. In addition, collaboration among BK teachers, homeroom teachers, Catholic Religious Education (PAK) teachers, and parents serves as a reinforcing factor that creates a sustainable support system for student discipline. The study concludes that BK teachers play a key role in instilling time discipline as part of students’ moral and religious character formation while contributing practical insights for the development of an integrative guidance and counseling model in secondary schools.